Master Teachers’ Experiences in Classroom Management, Teaching Strategies, Students’ Engagement, and Behavior in the Digital Era - Usman, Madznie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of Master Teachers in classroom management, teaching strategies, and student behavior in the digital era at Vitali National High School. Anchored on the view that effective classroom management is shaped by instructional practices, teacher-learner relationships, behavior management strategies, and teachers’ capacity to respond to changing classroom conditions, the study employed a qualitative phenomenological research design. Two Master Teachers from Vitali National High School were purposively selected as respondents because of their teaching experience, instructional leadership roles, and direct involvement in classroom management and learner engagement. Data were gathered using a researcher-made modified semi-structured interview guide, audio-recorded interviews, and field notes, and were analyzed through thematic analysis. Findings revealed that classroom management in the digital era requires adaptability, resilience, patience, innovation, and learner-centered practices. The participants used technology-supported and interactive strategies such as Google Classroom, Kahoot, Mentimeter, online quizzes, group discussions, breakout rooms, recorded lessons, differentiated activities, and follow-up tasks to promote engagement and address diverse learner needs. However, challenges such as unstable internet connection, limited gadgets, online distractions, lack of focus, absenteeism, low responsiveness, and limited parental support affected teaching and learning. The study concluded that effective digital-era classroom management requires inclusive, engaging, responsible, and supportive learning environments supported by teacher professional growth, parent collaboration, improved infrastructure, and equitable access to technology. The study aligns with SDG 4, Quality Education, by supporting improved teaching practices, learner engagement, and inclusive classroom instruction. It also relates to SDG 16, Peace, Justice, and Strong Institutions, by promoting orderly, respectful, and supportive learning environments. Its sustainability impact lies in strengthening educational and institutional practices through teacher development, mentoring, digital pedagogy, and responsive classroom management.
Keywords: Classroom Management; Digital Era; Learner-Centered Teaching; Master Teachers; Phenomenological Research; Student Behavior; Student Engagement; Teaching Strategies; Technology-Supported Instruction